"Age in Love": Falstaff among the Minions of the Moon [with illustrations]. (11th March 2013) - Vanhoutte, Jacqueline
<x xml:space="preserve">Abstract</x> This essay argues that a web of references binds Shakespeare's plump Jack to Elizabeth I's "men of good government" as they were represented in anti‐government tracts or Lyly's plays—especially the greatest minion of all, Robert Dudley, Earl of Leicester. Because courtly codes of conduct conflicted with expectations regarding age‐appropriate behavior, opposition works were able to portray Leicester as the embodiment of "age in love." Drawing on recent accounts of the emergence of a public sphere in England, this essay situates Falstaff within this strain of anti‐Leicestrian discourse, showing that he is a vehicle for thinking about the Elizabethan court and the theater's relation to that court. Among the old knight's salient features in this regard is his ability to incite judgment and to conjure a public defined by the willingness to engage in critical dialogue. The process that unites and elevates "men of all sorts" in the baiting of a figure associated with Elizabeth is democratizing but also gendered. The Falstaff plays turn the baiting of courtly old men into a profitable theatrical venture, thereby recalibrating the theater's relation to the structures of power and to the concepts of recreation and pleasure. (J.V.)